Effect of Sprinkler Type and Pump Operating Pressure in a Stationary Sprinkler Pump - Al-Safaar , Ali Hussein; Mukheef , Mohanad Jundi; Mohammed Ali Al-Zaidi, Ali Abdulqader; Sabah kamil , Yaseen (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
The modern irrigation method using small local sprinklers (fog spraying) is one of the methods that is recommended to be followed. Evaluate the performance of the sprinkler irrigation system in terms of water distribution over the irrigated area, where several different standards must be adopted to control the irrigation regularity. This study was conducted on agricultural land located in the region. The desert in Karbala Governorate, 100 km south of the capital, Baghdad, in the month of April 2023, to determine the effect of two factors, namely the type of sprinkler, where two types of short-range and more widely used sprinklers were used; The operating pressure of the pump has two levels (2 and 4) Bar, and their interactions in the coefficient of uniformity of water distribution, uniformity of distribution, and efficiency of water addition. The averages were tested and the results showed that there were differences in water distribution at the pillar sprinkler for both the water distribution coefficient and distribution efficiency, as it gave the best result for the water distribution uniformity coefficient of 75.951% and the water addition efficiency of 74.865%, while the (Al-Khairat) sprinkler was the best morally. The consistency of water distribution 68.716%. The results also showed that the pump's operating pressure was superior at 2 bar in all the characteristics studied at the operating pressure of 4 bar. In the three-way interaction between the treatments, the best value for the water distribution uniformity coefficient and water addition efficiency was when using the sprinkler with a pressure of 2 bar, where the distribution uniformity coefficient was 77.245% and the water addition efficiency was 70.985%, while the consistency of distribution was its best value. With the sprayer (Al-Khairat) and the pressure of 2 bar, this value reached 69.426%.